2022
DOI: 10.3390/pharmaceutics14091942
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL6R Genetic Variants in Predicting Response to Tocilizumab in Patients with Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a prevalent autoimmune disease characterized by chronic arthritis that may lead to irreversible joint damage and significant disability. Patients with RA are commonly treated with Tocilizumab (TCZ), an IL-6 receptor (IL-6R) antagonist, but many patients refractorily respond to this therapy. Identifying genetic biomarkers as predictors of TCZ response could be a key to providing a personalized medicine strategy. We aimed to evaluate whether functional single nucleotide polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…CC carriers of rs11265618 showed improved low disease activity rates at 12 months [ 28 ], while TT carriers of rs4329505 showed less joint swelling at three months [ 30 ]. Although we found similar trends relating to the same genotypes with efficacy outcomes at six months in our previous study, the results were not statistically significant [ 33 ].…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…CC carriers of rs11265618 showed improved low disease activity rates at 12 months [ 28 ], while TT carriers of rs4329505 showed less joint swelling at three months [ 30 ]. Although we found similar trends relating to the same genotypes with efficacy outcomes at six months in our previous study, the results were not statistically significant [ 33 ].…”
Section: Discussionsupporting
confidence: 45%
“…Our results regarding rs4845625 show that carriers of the T allele (TT + TC) had a higher incidence of dyslipidemia compared to CC carriers (36.7% vs. 16.7%) when treated with tocilizumab. A recent study of patients with RA by our group also described a greater response to tocilizumab treatment at six months in carriers of the TT or CT genotypes for rs4845625 [ 33 ]. Additionally, in line with our results, in 2017, Arguinano et al described an association between rs4845625*T and high levels of LDL in a healthy cohort, suggesting that IL6R genetic variations may constitute a cardiovascular risk factor [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning autoimmune and inflammatory diseases, Chernov et al observed a relationship between ABCB1 rs1045642, rs1128503, and rs2032582 and cyclosporine response in patients with psoriasis [ 26 ]. Furthermore, Sainz et al observed a relationship between IL6R rs4845625 and tocilizumab response in patients with rheumatoid arthritis [ 27 ]. In relation to the latter disease, Madrid-Paredes et al [ 28 ] reviewed the genetic, epigenetic, and environmental factors related to the response of disease-modifying antirheumatic drugs.…”
mentioning
confidence: 99%